Bundle care for prevention of recurrence of venous ulcer: scoping review (Research, Society and Development, 2023)
Objective: To identify the bundle cares to prevent the recurrence of venous ulcers, based on scientific evidence. Methods: Scope review carried out in the Medical Literature Analysis and Retrieval System Online/ National Library of Medicine, Scopus, CINAHL, CAPES, Cochrane and LILACS Catalog of Theses and Dissertations, between October 2021 and January 2022. The descriptors Varicose, Ulcer, Care, Recurrence, Varicose Ulcer (Varicose, ulcer, care, recurrence and varicose ulcer) were used. Eligibility criteria were: studies with no language restriction and no time frame, available in full text and focusing on measures to prevent recurrence of venous ulcers. Results: Five precautions for the prevention of venous ulcers were found: health education (booklets, pamphlets, e-learning, effective strategies for patient cooperation), compression therapy (appropriately sized stockings, medium or high compression, choosing the strongest possible according to tolerance, multilayer compression), lower limb care (elevating the legs from 30 minutes to four hours a day, moisturizing the skin, preventing accidents with the legs, avoiding long periods sitting or standing, and calf and ankle exercises and walking), nutrition (overweight control and knowledge about adequate nutrition) and invasive procedures (foam sclerotherapy associated with compression, radical debridement and grafting and surgical correction of venous insufficiency). All care must be carried out in an environment with follow-up and support (access to tests and consultations, specialized follow-up, social support and high levels of self-efficacy). Conclusion: acting by integrating care from different approaches is important to achieve effective prevention of recurrence of venous ulcers.